2002
DOI: 10.1210/jcem.87.5.8458
|View full text |Cite
|
Sign up to set email alerts
|

The Ectopic Expression of the Gastric Inhibitory Polypeptide Receptor Is Frequent in Adrenocorticotropin-Independent Bilateral Macronodular Adrenal Hyperplasia, but Rare in Unilateral Tumors

Abstract: Control of cortisol secretion by the abnormal expression of the gastric inhibitory polypeptide receptor (GIP-R) have been observed in some rare cases of ACTH-independent, food-dependent Cushing's syndrome (FD-ACS) due to adrenal adenoma (AA) or bilateral macronodular hyperplasia (AIMAH). This study was performed to determine the prevalence of GIP-R ectopic expression in ACS and its correlation with fasting cortisol levels. GIP-R expression was studied by RT-PCR in 30 unilateral adrenal tumors [16 AA and 14 adr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
2
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(32 citation statements)
references
References 26 publications
1
26
2
3
Order By: Relevance
“…Considering that ACTH could play a role in this disease, it was then suggested to name it PBMAH, to avoid the confusing reference to 'ACTH-independence' (3). The concept of illegitimate receptor expression was mostly demonstrated after the investigation of PBMAH patients, and this phenomenon is observed in the majority of PBMAH patients (1,4,5,6).…”
Section: Introductionmentioning
confidence: 99%
“…Considering that ACTH could play a role in this disease, it was then suggested to name it PBMAH, to avoid the confusing reference to 'ACTH-independence' (3). The concept of illegitimate receptor expression was mostly demonstrated after the investigation of PBMAH patients, and this phenomenon is observed in the majority of PBMAH patients (1,4,5,6).…”
Section: Introductionmentioning
confidence: 99%
“…Bertherat et al performed an in vivo and in vitro screening study for aberrant receptors in 4 consecutive patients with AIMAH and CS [85]: they reported 2 patients who responded to both GIP and hCG, 1 patient who responded to cisapride (5-HT4 receptor agonist) and upright posture in vivo and to serotonin, angiotensin II, and AVP in vitro, and 1 patient who responded to upright posture in vivo. In an in vitro screening study, the GIP receptor was found to be expressed in 4 of 8 adrenal glands from AIMAH patients and in only 1 of 16 unilateral adenomas [31]. Dall'Asta et al recently reported a higher frequency of aberrant cortisol responses in adrenal adenomas; he identified one or multiple aberrant responses in 3 of 4 patients with adrenal adenomas and overt CS [86].…”
Section: Frequency Of Aberrant Hormone Receptors In Adrenal Csmentioning
confidence: 98%
“…The presence of GIP receptors in the adrenal gland was further suggested by adrenal imaging following the injection of [ 123 I] GIP [24]. Since these initial descriptions, GIP-dependent CS has been described in at least 17 patients with AIMAH [21,[24][25][26][27][28][29][30][31] and 7 patients with unilateral adenomas [21,23,[32][33][34][35]. Interestingly, GIPdependent combined oversecretion of androgen and, to a lesser extent, of cortisol has been described in a patient with an adrenal adenoma and hirsutism [35].…”
Section: Food-and Gastric Inhibitory Polypeptide (Gip)-dependent Csmentioning
confidence: 99%
“…По данным ряда исследований, мето-дом проведения стимуляционных проб (на-пример, инсулиновая гипогликемия, при ем углеводистой пищи, стимуляция специальны-ми лигандами), иммуногистохимического и молекулярно-генетического исследований удаленного в ходе операции материала была идентифицирована экспрессия аберрантных или избыточно представленных рецепторов, а также их повышенная активность: рецепто-ры к глюкозозависимому инсулинотропному полипептиду (GIPR), β-адрено миметикам, ка-техоламинам (β-AR), вазопрессину (V1-3-AVPR или AVPR 1A, AVPR1B, AVPR2), лютеи-низирующему и хорионическому гонадо-тропному гормонам (LH/hCG-R), серотонину (5HT-4R или HTR4), ангиотензину II (AT-1R или AGR1), вазоинтестинальному пептиду (ВИП). В качестве стимулирующих агентов (лиганд) в исследованиях in vitro и in vivo использова-лись: очищенный хорионический гонадотро-пин (агонист к LH/hCG-R), цизаприд и мето-клопрамид (агонист 5HT-4R), норэпинеф-рин (адреномиметик), аргинин-вазопрессин (АВП), терлипрессин (агонисты к V1-3-AVPR), препараты гастроинтестинального пептида (ГИП) [74][75][76][77][78][79]. Автономная гипер продукция кортизола может быть вызвана наличием как одного, так и нескольких мембранных рецеп-торов, сопряженных с G-белком.…”
Section: тактика ведения и лечения пациентов с субклиническим синдромunclassified
“…торы) [83,87] либо уменьшения влияния стимулирующих факторов (терапия леупро-лида ацетатом приводит к подавлению син-теза ЛГ, введение аналога соматостатина октреотида нивелирует повышение корти-зола при ГИП-зависимой гиперсекреции кортизола) [78,88].…”
Section: список литературыunclassified